Pelvic organ prolapse and endogenous circulating sex steroids in postmenopausal women: A case control-study. (March 2017) - Bodner-Adler, Barbara; Bodner, Klaus; Schneidinger, Cora; Kimberger, Oliver; Halpern, Ksenia; Koelbl, Heinz; Umek, Wolfgang
Abstract: Objective: We compared sex steroid levels of postmenopausal patients with symptomatic pelvic organ prolapse (POP) with postmenopausal matched patients without any sign of POP. Furthermore, we evaluated a possible relationship between sex steroid levels and various urogynecologic parameters in cases with POP. Main outcome of interest were differences in circulating estradiol levels between the two groups. Study design: We conducted a case-control study and 46 postmenopausal women with symptomatic POP ≥ stage 2 were matched 1:1 with 46 urogynecologic healthy women. Blood samples were drawn from all patients for assessment for estradiol (E2), Follicle-stimulating hormone (FSH), Luteinizing hormone (LH), testosterone (T), androstendion (AEON), dehydroepiandrosterone sulphate (DHEAS) and sex hormone binding globulin (SHBG) with an Electrochemiluminescence immunoassay. Results: Our study failed to show any statistically significant differences in sex steroid levels between women with and without POP (p > 0.05). However, serum concentration of E2 (p < 0, 0001), free testosterone (p = 0, 034) and DHEAS (p = 0, 024) was statistically significant lower in patients with severe prolapse stage. Serum levels of E2 were statistically significant higher in cases with moderate-strong Oxford Grading Scale (p < 0, 0001). Low circulating E2 (p = 0, 019) as well as menopausal age (p = 0, 022) remained independent risk factors for POP in multiple logistic regression analysis. Conclusion: The significant low hormonal levels in cases with high POP-Q stage as well as the significant higher estradiol levels in patients with strong Oxford Grading Scale may indicate that endogenous circulating sex steroids might have a potential role in the severity and progression of POP.